Label-Free Proteomic Approach to Study the Non-lethal Effects of Silver Nanoparticles on a Gut Bacterium - Domingo, Guido; Villa, Federica; Vannini, Candida; Garuglieri, Elisa; Onelli, Elisabetta; Bracale, Marcella; Cappitelli, Francesca (Frontiers in Microbiology, 2019)
Among all the food-related nanoparticles consumed every day, silver nanoparticles (AgNPs) have become one of the most commonly utilized, because of their anti-microbial properties. Despite their common use, the effects of sub-lethal concentrations of AgNPs, especially on gut biofilms, have been poorly investigated. To address this issue, we investigated in vitro the proteomic response of a mono-species Escherichia coli gut biofilm to chronic and acute exposures in sub-lethal concentrations of AgNPs. We used a new gel- and label-free proteomic approach based on shotgun nanoflow liquid chromatography-tandem mass spectrometry (LC-MS/MS). This approach allows a quantification of the whole proteome at a dynamic range that is higher than the traditional proteomic investigation. To assess all different possible exposure scenarios, we compared the biofilm proteome of four treatments: i) untreated cells for the control treatment, ii) cells treated with 1 μg/mL AgNPs for 24 h for the acute treatment, iii) cells grown with 1 μg/mL AgNPs for 96 h for the chronic treatment, and iv) cells grown in the presence of 1 μg/mL AgNPs for 72 h and then further treated for 24 h with 10 μg/mL AgNPs for the chronic+acute treatment. Among the 1917 proteins identified, 212 were significantly differentially expressed proteins. Several pathways were altered including biofilm formation, bacterial adhesion, stress response to reactive oxygen species (ROS), and glucose utilization.